The Methodology of Ibn Aqil and Al-Ashmouni in Explaining Ibn Malik’s Alfiyyah: A Descriptive Analytical Comparative Study (Comprehensive Journal of Science, 2026)
This research examines the methodology of both Ibn Aqil and Al-Ashmouni in explaining Ibn Malik’s Alfiyyah, one of the most famous educational poetic texts in Arabic grammar and one of the most influential works in the development of grammatical studies. The study aims to introduce Ibn Malik and his Alfiyyah, clarify its scholarly status, and then present Ibn Aqil and Al-Ashmouni as two major commentators. It also seeks to explore each commentator’s method in presenting grammatical material, explaining the poetic verses, using grammatical evidence, and discussing controversial issues. The research adopts the descriptive analytical method, based on presenting, analyzing, and comparing the features of the two commentaries. The study shows that Ibn Aqil’s commentary is characterized by its educational nature, clarity, simplicity of expression, and avoidance of excessive detail and complex grammatical disputes, making it suitable for students and beginners. In contrast, Al-Ashmouni’s commentary is encyclopedic, rich in evidence, explanations, notes, and grammatical opinions, making it more detailed and useful for specialists. The research concludes that both commentators preserved the order and structure of Ibn Malik’s Alfiyyah, but Ibn Aqil tended toward simplification and conciseness, while Al-Ashmouni tended toward expansion and comprehensiveness. Thus, the two commentaries complement each other in serving the Alfiyyah and Arabic grammatical studies.
Keywords: Ibn Malik’s Alfiyyah, Ibn Aqil, Al-Ashmouni, grammatical commentaries, grammatical methodology, Arabic grammar